CAUSAL AND INFLUENCE ANALYSIS OF FDI FLOW TO CHINA USING FUZZY COGNITIVE MAPS (CASE STUDY 1998-2016) - Wulandari, Pandam Rukmi (Universitas Gunadarma, 2020)
China as a major emerging market, is attracted significant flows of Foreign Direct Investment (FDI) to become second largest receipt. This research briefly examines the determinants of FDI obtained from literature and secondary data from World Bank and Global Competitiveness Index within 1998-2016, updating from prior research within 1996-2012. Fuzzy Cognitive Maps (FCMs) is employed as an analysis method to investigate the causal-effect relationships between the determinants by the application of soft computing technique of FCM using FCMMappers. Furthermore, FCM simulation of concepts/parameters change to understand the c ausal influence amongst concepts. The FCM simulation handle efficiently with complex modeling problems to assess determinants of FDI Flow to China.